Rugemødre, rejser og nye reproduktionsmetaforer. Weblogs om transnationalt surrogatmoderskab - Madsen, Karen Hvidtfeldt (K&K - Kultur og Klasse, 2012)
SURROGACY MOTHERS, TRAVELS AND NEW REPRODUCTION METAPHORS | Surrogacy is a growing industry in India, as still more infertile couples, homosexual couples and singles from the Western world, travel abroad to fulfill their dream of having a baby. Indian clinics offer highly specialized services in exotic surroundings, an obliging culture and legislation, and remarkably low payments. This article examines and discusses how the conception of motherhood is constructed in public weblogs narrated by parents and intended parents of Indian surrogate children. The chapter aims at analyzing the rhetorical, narrative and metaphorical strategies of the blogs, focusing on how the biological aspects of motherhood (for instance pregnancy and giving birth) and the transnational aspects are negotiated and reinterpreted in the present context of globalization, tech nological possibilities and consumer culture.